Miguel Ángel Asturias, El árbol de la Cruz. Ed. facs. coord. por A. Janquart y A. Segala. ALLCA XX-F.C.E. España, Madrid, 1993; 330 pp. (Colección Archivos/Hispanística XX, 24). - Franco, Lourdes (El Colegio de México, 1996)
Se reseñó el libro: El árbol de la Cruz.